2003
DOI: 10.1007/s00204-003-0492-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of daily stress or repeated paraoxon exposures on subacute pyridostigmine toxicity in rats

Abstract: Pyridostigmine (PYR) is a carbamate cholinesterase (ChE) inhibitor used during the Persian Gulf War as a pretreatment against possible chemical nerve agent attack. Because of its quaternary structure, PYR entry into the central nervous system is limited by the blood-brain barrier (BBB). Following reports of unexplained illnesses among Gulf War veterans, however, central nervous system effects of PYR have been postulated through either stress-induced alteration of BBB permeability or via interactions with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In the adult, concurrent stress augments the systemic toxicity and neurotoxicity of organophosphates (Basha and Poojary, 2011, 2012; Pung et al, 2006; Shaikh et al, 2003) but to our knowledge, there are no corresponding studies for stress in pregnancy. Here, the prenatal stressor was the surgical procedure to insert the minipumps.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult, concurrent stress augments the systemic toxicity and neurotoxicity of organophosphates (Basha and Poojary, 2011, 2012; Pung et al, 2006; Shaikh et al, 2003) but to our knowledge, there are no corresponding studies for stress in pregnancy. Here, the prenatal stressor was the surgical procedure to insert the minipumps.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we have formulated self-decontaminating composite paints that encapsulate highly active and stable bionanoconjugates of OPH for decontamination of paraoxon, a chemical simulant of V-type, and diisopropylfluorophosphate (DFP), a chemical simulant of G-type, nerve agents, both potent irreversible acetylcholinesterase inhibitors. Exposure to paraoxon or DFP can produce acetylcholinesterase inhibition 21 and compromise the blood-brain barrier. 22 We showed that composites containing only 0.07% (w/w) OPH render [99% decontamination of paraoxon after 30 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…First, these agents are given as the consensus treatment for preterm labor occurring between 24 and 34 weeks of gestation in order to prevent respiratory distress syndrome (Gilstrap et al, 1995); currently, one of every ten newborns in the U.S. has undergone this treatment (Matthews et al, 2002). Second, endogenous glucocorticoid release from stress can enhance the systemic toxicity of organophosphates or other toxicants (Aisa et al, 2009; Colomina et al, 1995; Pung et al, 2006; Shaikh et al, 2003). By themselves, excess glucocorticoids have an adverse impact on the numbers of neurons, structure and synaptic connectivity in the immature brain, ultimately contributing to a variety of neuroendocrine, behavioral and cardiovascular disorders (Cavalieri and Cohen, 2006; Drake et al, 2007; Meyer, 1985; Moritz et al, 2005; Pryce et al, 2011; Rokyta et al, 2008; Tegethoff et al, 2009).…”
Section: Introductionmentioning
confidence: 99%